PENGARUH PERBEDAAN WARNA WADAH PEMELIHARAAN TERHADAP KELANGSUNGAN HIDUP DAN PERTUMBUHAN BENIH IKAN SEMAH (Tor douronensis) - Fairisal Oktavi Hidayat; Azrita Azrita; Hafrijal Syandri (Universitas Teuku Umar, 2026)
This study elaborates the effect of different rearing container colors on the survival rate and growth performance of Tor douronensis juveniles. The experiment was conducted for 90 days using a Completely Randomized Design (CRD) with five treatments and three replications. The treatments consisted of transparent, orange, yellow, blue, and dark green container colors. The observed parameters included survival rate (SR), daily weight growth (WGR), daily length growth (LGR), specific growth rate (SGR), condition factor (K), coefficient of variation (CV), feed conversion ratio (FCR), and water quality. Result revealed that container color significantly affected (P<0.05) survival rate and most growth parameters, while no significant effect was observed on FCR (P>0.05). The yellow container treatment consistently showed the best performance, with the highest LGR (5.34±0.06 mm/day), SGR (2.29±0.04%/day), and survival rate (98.67±2.31%). Bright-colored container enhanced fish visibility and feeding efficiency, leading to better growth and reduced stress. In contrast, darker-colored container resulted in lower performance, presumably due to reduced light reflection and increased stress levels. Water quality parameters remained within the optimal range throughout the study, indicating that container color was the primary factor influencing fish performance. In conclusion, bright-colored container, particularly yellow, significantly enhanced the survival rate and growth performance of Tor douronensis juveniles. Manipulating container color is a simple and cost-effective strategy to improve productivity in freshwater fish farming. Keywords: Tor douronensis, container color, growth, survival